Evaluation of speed change in 100 m sprint running - Saito, Y.; Nagahara, R.; Ae, M.; Matsuo, A. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to propose a method to evaluate speed in 100m running with modified exponential equations. The speed changes in 100m sprint race of ninetysix sprinters (62 men and 34 women) were measured with a LAVEG system. The 100m race was divided into the acceleration and deceleration phases based on the maximum speed, and speed were estimated. 1) The exponential equations proposed in this study well estimated the speed change pattern of the 100m on the different record groups. The average errors between the official time and the time estimated were 0.024±0.040s in men and 0.04±0.039 in women. 2) The maximum speed was the most important factor for both men and women sprinters to achieve best performance the race. 3) The men world class sprinters accelerated quickly (large k), but reached the maximum speed later than the other sprinters, which resulted in shorter deceleration phase and smaller decreases in speed after reaching the maximum speed.